2008
DOI: 10.1152/jn.01141.2007
|View full text |Cite
|
Sign up to set email alerts
|

Acquisition of the Temporal and Ordinal Structure of Movement Sequences in Incidental Learning

Abstract: O'Reilly JX, McCarthy KJ, Capizzi M, Nobre AC. Acquisition of the temporal and ordinal structure of movement sequences in incidental learning. J Neurophysiol 99: 2731-2735, 2008. First published March 5, 2008 doi:10.1152/jn.01141.2007. We investigated the acquisition and integration of temporal and ordinal sequence information in an incidental learning model of motor skill acquisition (the serial reaction time task). Human participants were exposed to a stimulus-response sequence that had temporal structure, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

11
114
4

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 65 publications
(129 citation statements)
references
References 18 publications
11
114
4
Order By: Relevance
“…The lack of measureable increases in trained sequence performance in just the timing-response hand (RH) may suggest that learning of a timing sequence independent of ordinal action responding is not occurring here, and is in line with previous reports (O’Reilly et al, 2008; Shin & Ivry, 2002). Alternately, the lack of transfer may be related to the fact that the timing response is made after the initial order response since the left-hand button press (order) is the first part of a two-part response which precedes an accurately timed right-hand strum.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…The lack of measureable increases in trained sequence performance in just the timing-response hand (RH) may suggest that learning of a timing sequence independent of ordinal action responding is not occurring here, and is in line with previous reports (O’Reilly et al, 2008; Shin & Ivry, 2002). Alternately, the lack of transfer may be related to the fact that the timing response is made after the initial order response since the left-hand button press (order) is the first part of a two-part response which precedes an accurately timed right-hand strum.…”
Section: Discussionsupporting
confidence: 90%
“…Transfer was not found in the O N T P condition even though the individual timing response characteristics did not change from the trained condition. The partial performance transfer of order (when timing was changed) but not timing (when order was changed) fits with previous SRT work suggesting that timing is merely a component of an action order sequence which is not learned independently (O’Reilly et al, 2008; Shin & Ivry, 2002). …”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…The latter happens, for instance, when the rhythm of a song is used to sing different melodies. Studies using uncorrelated temporal sequences (Buchner & Steffens, 2001;O'Reilly, McCarthy, Capizzi, & Nobre, 2008;Shin & Ivry, 2002) found that they are typically not learned in an incidental manner. For instance, Shin & Ivry (2002) analysed the learning of seven-and eight-element temporal sequences embedded in eight-element ordinal sequences, and found that only eight-element (correlated) temporal sequences were learned.…”
mentioning
confidence: 99%
“…5 learning. Concerning uncorrelated temporal sequences, it was first suggested that they are not learned because temporal representations are dependent on ordinal ones when learning is incidental (O'Reilly, McCarthy, Capizzi, & Nobre, 2008). However, Ullén and Bengsston (2003) provided an alternative explanation.…”
mentioning
confidence: 99%